Data model management, with the use of artificial intelligence, for a geographic information system in the energetic sector - Sánchez Fleitas, Nayi; Comas Rdoríguez, Raúl; García Lorenzo, María Matilde; Riverol Quesada, Amanda (Enfoque UTE, 2016)
A Geographic Information System (GIS), named SIGOBE v 3.0, for the electric sector is development. The Integral Management System of the ECIE (SIGECIE) and the Integrated Network Management System (SIGERE) databases are taxed alfanumeric information. Studies determined the need for a model for data management, contributing to the GIS development, on a conceptual schema domain capable of responding to different user requests, through automatic query as support decision making. To provide the GIS with a conceptual basis an ontology is determined, which will be expressed by logical descriptive, to generate the traits of a case-based reasoning that allows automation of consultations. The final quality of GIS was verified according to the quality standards of the ISO-9126:2002 standard. The proposed model and its functionality contributes to: facilitate decision-making at different levels, perform risk analysis to have the defects of electrical installations, reduce the time of failure to the key areas of the country, organize the travel of trucks more efficiently and locate electrical faults more accurately.